Peran Kebijakan Pemerintah Dalam Mendorong Pertumbuhan Industri Manufaktur - Bella Fasta’sima; Hafizhah Hasna Zaharani; Wildan Ubaydilah Widodo; Naerul Edwin Kiky Aprianto (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
The manufacturing industry is still the main driver of the national economy. This is reflected in the consistency of the non-oil and gas processing industry which makes the largest contribution to the national gross domestic product (GDP) with an achievement of 16.30 percent in the second quarter of 2023. The ability of the manufacturing sector to provide traded goods and jobs makes it a significant contributor to Indonesia's economic situation. The Indonesian government has taken various steps to increase competitiveness in industries that are considered strategic in facing liberalization towards the ASEAN Single Market, including the manufacturing sector. One of the most important economic sectors for Indonesia is the manufacturing sector. Apart from exports and its contribution to GDP which continues to increase, the manufacturing sector is a labor-intensive sector that absorbs a lot of workers.